Fulminant neuromyelitis optica in a Finnish woman – a case report - Kaivorinne, Anna‐Lotta (Clin Case Rep, 2016)
Neuromyelitis optica is a rare inflammatory, demyelinating disease of the central nervous system that predominantly targets the optic nerves and spinal cord. Our case represents an unusual and severe course of neuromyelitis optica. Despite several forms of treatment, our patient died after a severe and short‐term attack.